Personagens políticos e opinião pública nas eleições para governador do estado do Espírito Santo em 1994 - Barcellos, Felipe da Costa (2022)
In the present dissertation, we made a study about the elections for governor of the state of Espírito Santo in 1994. Specifically, we dealt with the candidates who were the main protagonists of the aforementioned election: Vitor Buaiz (PT) and Cabo Camata (PSD). Buaiz was known for his thoughtful and conciliatory way of doing politics, especially during his tenure as mayor of Vitória (1989-1992). And Camata, seen as an outsider in the political game of the elites of Espírito Santo, was a controversial figure, who became notable as a staunch supporter of the police category and for proposing extremist solutions to the various problems that affect society, especially in terms of public security. We start from the hypothesis that the success of the two candidacies stems from the fact that Buaiz and Camata are the political characters most compatible with the state conjuncture of 1994, as well as their political alliances throughout the election and the difficulties faced by the other candidates in that election. To prove this perspective, we carried out an analysis based on journalistic sources, magazines and interviews, based of authors who have dedicated themselves to the study of electoral campaigns, political characters, voter behavior and the political history of Espírito Santo, such as Alberto Carlos Almeida (2008), Roger Schwartzenberg (1978), Emerson Urizzi Cervi (2012), Marcus Figueiredo (2008) and Ueber José de Oliveira (2008). As a result of the research, we found that Vitor Buaiz presented himself to the population with the image of a good, competent and responsible manager, and Cabo Camata as the candidate of public security, capable of combating the high rates of violence in Espírito Santo through more severe punishments for criminals. Understanding this difference in profiles, in tune with the political articulations of the two candidates, the game of interests underlying their campaigns and the movements of other political actors in the electoral dispute, offers an explanatory framework for the success of Buaiz and Camata in that election, and helps to elucidate the sociopolitical scenario of Espírito Santo in the mid-1990s.